Adaptive Compensator of Single State Elastoplastic Friction Model - A. A. Abouelsoud; J. Abdo; R. Zaier (The Journal of Engineering Research, 2011)
A nonlinear friction is an unavoidable phenomenon frequently experienced in mechanical system between two contact surfaces. An adaptive compensator is designed to achieve tracking of a desired velocity trajectory in the presence of friction force described by a single state elastoplastic friction model. The adaptive compensator includes an adaptive observer and a computed force controller. The closed loop system is shown to be stable using Lyapunov second method. Simulation results show the effectiveness of the proposed compensator.